TAX JURISDICTION OF COMMUNES IN POLAND AND METHODS OF ITS IMPLEMENTATION - Dorota Burzyńska (Polityki Europejskie, Finanse i Marketing)
The aim of the study was to determine the possibility of using methods of implementing the tax gov-ernance of municipalities in the field of local taxes and to assess the importance of using government for the financial planning of the municipality in the conditions of the financial crisis. In order to achieve the goal, 60 randomly selected communes of various types were analyzed. The following methods were used: literature analysis, analysis of local legal acts, in-depth interviews, and statis-tical studies. Data for the years 2019-2021 was used for the analysis. On the basis of the analyzed material, it was found that there is a diversified scope of using the methods of tax governance in communes. Tax jurisdiction is an important factor influencing the financial policy of communes in the opinion of the respondents, but the use of these methods in practice in the analyzed period was very limited. The analyses show that the communes perceive the risk of legal and financial changes, and most do not use the methods of exercising power due to limited income and an increase in expenses related to the crisis after the pandemic.